Treatment of acute migraine attacks in children with analgesics on the World Health Organization Essential Medicines List: A systematic review and GRADE evidence synthesis. (August 2018) - Jeric, Milka; Surjan, Nives; Jelicic Kadic, Antonia; Riva, Nicoletta; Puljak, Livia
Background: The World Health Organization Essential Medicines List (WHO EML) contains two analgesics for treatment of acute migraine attacks in children, ibuprofen and paracetamol. Methods: The Embase, CDSR, CENTRAL, DARE and MEDLINE databases were searched up to 18 April 2017. We analyzed randomized controlled trials (RCTs) and systematic reviews (SRs) that investigate the efficacy and safety of ibuprofen or paracetamol for treatment of acute migraine attacks in children. We conducted meta-analysis and assessments of evidence with GRADE, Cochrane risk of bias tool, and AMSTAR. Results: Three RCTs (201 children) and 10 SRs on ibuprofen and/or paracetamol for acute migraine attacks in children were included. Meta-analysis indicated that ibuprofen was superior to placebo for pain-free at 2 h or pain relief at 2 h, without difference in adverse events. There were no differences between paracetamol and placebo, or ibuprofen and paracetamol. Ten SRs that analyzed various therapies for migraine in children were published between 2004 and 2016, with discordant conclusions. Conclusion: Limited data from poor quality RCTs indicate that ibuprofen and paracetamol might be effective analgesics for treating migraine attacks in children. Inclusion of ibuprofen and paracetamol as antimigraine medicines for children in the WHO EML is supported by indirect evidence from studies in adults.